Power Dynamics and Social Relations in Law Enforcement: A Critical Theory Perspective on the Ferdy Sambo Case - Bone, Sholihin; Fitri, Rizki Rahayu; Cahyaning, Citra; Solehuddin, Solehuddin; Maria, Anna (Constitutional Law Review, 2024)
This study analyzes the verdict in the Ferdy Sambo case through the lens of Critical Theory and Habermas' deliberative democracy to understand how law operates within power structures. Using a qualitative, critical-legal approach based on Habermas' framework, it examines court decisions, media reports, and institutional dynamics. The findings reveal that law is influenced by political and institutional dynamics rather than being fully neutral. The Supreme Court’s reduction of Ferdy Sambo’s sentence from death to life imprisonment reflects institutional compromise to preserve social stability and the police’s image. Technological manipulation, such as CCTV footage deletion, and public and media pressures during the trial further illustrate how legal communication is distorted by power relations. The study highlights the need for legal reforms beyond procedural aspects, emphasizing more democratic and inclusive communication mechanisms. Referring to Habermas' theory, it stresses that transparency and accountability are crucial to prevent law from merely legitimizing elite interests and to promote law as a means of social emancipation